Soil quality index (SQI) for assessing soil health of agroforestry system: Effect of Hardwickia binata Roxb. tree density on SQI in Bundelkhand, central India - Prasad, Rajendra; Newaj, Ram; Singh, R.; ., Ajit; Saroj, N.K.; Tripathi, V.D.; Shukla, Ashok; Singh, Prashant; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
Agroforestry land use is viewed as an optimal formula for restoration and revitalization of degraded land resource considering soil conservation value as its basic tenet. However, revitalization of soil resources is guided by complex array of positive and negative interactions, and strategies to manage them for maximum benefits. Assessment of soil quality by developing a composite soil quality index (SQI) based on soil indicators may provide answers to such concerns. In this background, the present study was conducted in a well established 20 years old Hardwikia binata Roxb. Based agroforestry system, aiming to evaluate effect of tree densities on SQI and how soil quality indicators respond in respect to tree density. The trial consisted of four treatments viz., control (pure crop), 200, 400 and 800 trees/ha. To develop SQI, representative soil samples were drawn from 0-30 cm depth from all plots and analysed for identified data set of indicators. Increase in tree density of H. binata has shown favourable effect on most of the studied indicators. Maximum SQI was observed in density of 800 trees/ha while minimum in control. In comparison to baseline, the improvement in SQI was minimum in control (6.8%) and maximum in agroforestry plot (35.1%) having density of 800 trees/ha. The improvement in soil quality over control ranged from 17.2 in 200 trees/ha to 30.4% in 800 trees/ha. The computed value of SQI ranged from 0.355 to 0.547 and had sensitivity of 1.54, reflecting its sensitiveness to density management. The infiltration rate (water movement), available K, and biological activity appeared to be sensitive and critical indicators for soil health in Bundelkhand region of central India.